2014
DOI: 10.1371/journal.pone.0107903
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Humoral Immune Responses to Blood-Stage Malaria Antigens following ChAd63-MVA Immunization, Controlled Human Malaria Infection and Natural Exposure

Abstract: The development of protective vaccines against many difficult infectious pathogens will necessitate the induction of effective antibody responses. Here we assess humoral immune responses against two antigens from the blood-stage merozoite of the Plasmodium falciparum human malaria parasite – MSP1 and AMA1. These antigens were delivered to healthy malaria-naïve adult volunteers in Phase Ia clinical trials using recombinant replication-deficient viral vectors – ChAd63 to prime the immune response and MVA to boos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
44
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 83 publications
11
44
2
Order By: Relevance
“…Consistent with other ChAd63-MVA malaria vaccines (43,52,63), the anti-RH5_FL serum IgG response was largely composed of IgG1 and IgG3, with moderate avidity as measured by NaSCN displacement ELISA. A study of naturally exposed individuals in Mali reported that the predominant IgG isotype detected against RH5 was IgG3 (23).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Consistent with other ChAd63-MVA malaria vaccines (43,52,63), the anti-RH5_FL serum IgG response was largely composed of IgG1 and IgG3, with moderate avidity as measured by NaSCN displacement ELISA. A study of naturally exposed individuals in Mali reported that the predominant IgG isotype detected against RH5 was IgG3 (23).…”
Section: Discussionsupporting
confidence: 84%
“…IgG antibody avidity was assessed by NaSCN displacement ELISA using previously described methodology (63), except that plates were coated with recombinant RH5_FL produced from the Drosophila S2 cells at 2 μg/ml. The concentration of NaSCN required to reduce the OD 405 (optical density measured at 405 nm)to 50% of that without NaSCN was used as a measure of avidity (IC 50 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isotype ELISAs were conducted as previously described 53 except plates were coated with 0.5 μg/mL of TRAP antigen in carbonate-bicarbonate coating buffer and left overnight at 4°C. Briefly, sera were diluted 1:100 in 0.2% BSA in PBS/Tween-20 (dilution buffer) and added in duplicate to each of six 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…This interpretation assumes, probably incorrectly, that anti‐MSP1 is representative of all antibody specificities in a given patient. Antibodies to both MSP1 and AMA‐1 are known to be relatively protective (growth‐inhibitory activity) in semi‐immune individuals and are responsive to natural parasite stimulation, but they are unlikely to be involved in parasite clearance . A weakness of our study is that anti‐MSP‐1 is probably unrelated to parasite clearance.…”
Section: Discussionmentioning
confidence: 89%